2007
DOI: 10.1002/chir.20389
|View full text |Cite
|
Sign up to set email alerts
|

Chiral crystallization of glutamic acid on self assembled films of cysteine

Abstract: In this article, we describe the preparation and use of chiral surfaces derived from enantiomerically pure crystals of amino acids. For this purpose, we chose to employ a self-assembly process to grow nanoscale chiral films of (+)-L or (-)-D cysteine, onto gold surfaces. We utilized those chiral films as resolving auxiliaries in the crystallization of enantiomers from solutions. To demonstrate the chiral discriminating ability of the chiral surfaces in crystallization processes, we investigated the crystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 54 publications
3
39
0
Order By: Relevance
“…Our basic hypothesis is that the chiral polymeric nanoparticles will act as selective chiral nuclei and lead to enantioselective crystallization of one enantiomer onto the polymeric nanoparticles. The assumption is supported by previous research on the enantioselective crystallization of l ‐glutamic acid on chiral self‐assembled multilayers surfaces . We studied the enantioselective crystallization of amino acids because they are the basis of all life processes and crystallization is one of the key steps in their preparation.…”
Section: Size and Molecular Weight Of The Prepared Polymer Nanoparticlesmentioning
confidence: 88%
“…Our basic hypothesis is that the chiral polymeric nanoparticles will act as selective chiral nuclei and lead to enantioselective crystallization of one enantiomer onto the polymeric nanoparticles. The assumption is supported by previous research on the enantioselective crystallization of l ‐glutamic acid on chiral self‐assembled multilayers surfaces . We studied the enantioselective crystallization of amino acids because they are the basis of all life processes and crystallization is one of the key steps in their preparation.…”
Section: Size and Molecular Weight Of The Prepared Polymer Nanoparticlesmentioning
confidence: 88%
“…The stability of the SAM surfaces was previously detected, presenting high and long-term chemical stability for the duration of the experiments. 3 Cell Culture. Culturing method has been previously described; 46 briefly, neurons were isolated from the CNS of adult medicinal leeches Hirudo medicinalis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After removal from solution, the substrates were rinsed with copious amounts of deionized water and blow dried with nitrogen. Self assembled monolayers of cysteine on gold have been previously studied using X‐ray photoelectron spectroscopy (XPS) and Scanning Tunneling Microscopy (STM) 14, 18. It has been reported that cysteine molecules are absorbed onto gold through the sulfur atom, while leaving the other two groups (COOH and NH 2 ) free.…”
Section: Methodsmentioning
confidence: 99%
“…Naturally chiral bulk crystalline surfaces have been shown to display chiral selectivity when immersed in a racemic solution 13. Self‐assembled monolayers of (+)‐ L and (−)‐ D cysteine on gold substrates were used as resolving auxiliaries in the crystallization of rac‐glutamic acid (a conglomerate) and rac‐histidine (a racemic compound) 14, 15. Similarly, chiral discrimination between ( R )‐ and ( S )‐thalidomide enantiomers was achieved using SAMs of ( R )‐ and ( S )‐1,1′‐binaphthalene‐2, 2′‐dithiol (BNSH) 16.…”
Section: Introductionmentioning
confidence: 99%